TRIM24 regulates chromatin remodeling and calcium dynamics in cardiomyocytes - Neu, Marco; Deshpande, Anushka; Borlepawar, Ankush; Hammer, Elke; Alameldeen, Ahmed; Vöcking, Phillipp; Seeger, Timon; Hausmann, Michael; Frey, Norbert; Rangrez, Ashraf Yusuf (Cell communication and signaling, 2025)
Background Cardiomyocyte proteostasis and calcium homeostasis are critical for maintaining cardiac function, with their dysregulation contributing to cardiac hypertrophy and heart failure. The Tripartite Motif Protein 24 (TRIM24), a well-characterized chromatin reader and transcriptional regulator in cancer, has recently emerged as a potential player in cardiac biology. However, its precise role in cardiomyocytes remains unclear. Using molecular, structural and functional approaches, this study investigates the impact of TRIM24 on cardiomyocyte function and gene regulation. - Methods To dissect the molecular and functional role of TRIM24, we conducted RNA-sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq) in neonatal rat ventricular cardiomyocytes (NRVCMs) to identify TRIM24-regulated pathways and transcriptional targets. Super-resolution microscopy and proteomics analysis were employed to examine its influence on chromatin organization and calcium-handling protein distribution. Calcium imaging and cardiomyocyte contractility assays were performed in both NRVCMs and human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) to assess functional effects. Additionally, NFAT activity was assessed to investigate its role in TRIM24-mediated hypertrophic signaling. - Results Through RNA-seq and ChIP-seq, we identified TRIM24 as a bidirectional transcriptional regulator, predominantly acting as a repressor but also exhibiting context-dependent activation of genes involved in e.g. cytoskeletal organization and calcium signaling. ChIP-seq identified TRIM24 binding at the NFATc4 locus, validated by motif analysis, while functional studies revealed that TRIM24 regulates NFATc4 protein levels and activity, enhancing upon overexpression and reducing upon knockdown. Furthermore, TRIM24 overexpression altered the expression and organization of Ryanodine Receptor 2 (RyR2), Sarcoplasmic/endoplasmic Reticulum Ca2+ ATPase 2a (SERCA2a), and Calsequestrin 1 (CASQ1), leading to calcium-handling defects. Super-resolution microscopy revealed a loss of chromatin organization and altered clustering of calcium-handling proteins. Despite a reduction in SERCA2a levels, TRIM24 activated the PI3K-AKT/PLN pathway, increasing phospholamban phosphorylation and compensatory calcium reuptake. In functional assays, TRIM24 overexpression increased beating frequency and calcium cycling in both NRVCMs and iPSC-CMs. - Conclusion Our findings establish TRIM24 as a novel regulator of chromatin remodeling and cardiomyocyte transcription, directly influencing calcium homeostasis and contractility, with potential implications for cardiac disease.